Dietary supplementation with a mixture of herbal extracts during late gestation and lactation improves performance of sows and nursing piglets through regulation of maternal metabolism and transmission of antibodies - Wang, Li; Huo, Bin; Huang, Lingjie; Che, Lianqiang; Feng, Bin; Lin, Yan; Xu, Shengyu; Wu, De; Fang, Zhengfeng (Frontiers in Veterinary Science, 2022)
The dietary inclusion of phytogenic feed additives to improve the performance and health of sows is considered to be safe, effective and environmentally friendly, thus gaining growing popularity among new strategies. This study was designed with three trials aimed to determine the effective supplemental levels of Scutellaria baicalensis and Lonicera japonica mixed extracts (SLE) in sow diets based on production performance and explore its related mechanisms of action based on serum metabolites, antioxidant capacity, and immune profile of sows and nursing piglets. Trials 1 and 2 were conducted to determine the effective dose and ratio of SLE by supplementation of various proportions and doses of SLE to sows diets from the late pregnancy to weaning, with litter performance at farrowing and weaning and disease conditions being evaluated. Trial 3 was conducted to further explore the mechanisms of action of SLE as evaluated by serum immunity and antioxidants indices in late gestation and lactation sows. The results of trials 1 and 2 showed that dietary supplementation of 1.0g/kg SLE (50% S. baicalensis extract, 30% L. japonica extract, and 20% wheat bran fiber as carrier) enhanced the number of piglets born alive, litter birth weight, litter weight gain, and average daily feed intake of sows during lactation, while decreased diarrhea of suckling piglets. In Trial 3, compared with the control group, dietary SLE supplementation increased (P < 0.05) sow serum glucose (GLU), triglyceride (TG), total cholesterol (TC), prolactin (PRL) and interleukin-10 (IL-10) concentrations, and total superoxide dismutase (T-SOD) activities at the farrowing, and increased (P < 0.05) sow serum PRL, leptin, and insulin (INS) concentrations at d 14 of lactation. Fat concentrations in sow colostrum and in milk on day 14 of lactation, both IgA and IgG concentrations in colostrum, and both IL-10 and IgA concentrations in piglet serum at d 14 of lactation were all increased (P < 0.05) following dietary SLE supplementation. Altogether, dietary supplementation with the appropriate levels of SLE promoted health and growth of suckling piglets, which was associated with the improvement of maternal metabolism and transmission of antibodies.